Anabolic Steroid use in Sports and in Physical Activity: Overview and Analysis - Filomena Mazzeo (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
Anabolic steroids,commonly referred to as anabolic androgenic steroids (AAS), are a family of hormones that comprises testosterone. Exposure to these substances can result in damage to human health, such as liver cancer, and to the environment. This class of doping substances cause an extensive increase in the muscular massandis being used to improve athletic performance. Athletes are still using them to increase physical performance and bodybuilders are using them to improve size and cosmetic appearance. For performance enhancing use, these substances generally used without interruption and during several weeks preceding a competition. The preferred method is "piling up" oral ingestion and injections.This type of treatment has been used in sport medicine to manage a variety of joint, tendon and soft tissue injuries.The long-term side eff ects of anabolic steroids are severe and will depend on dosage and duration. In particular, early death from cardiovascular disease, sterility in men and, in women, masculinization and possible irreversible eff ects constitute the most serious dangers. More recently, studies have suggested that psychological and behavioral changes and addiction may result from chronic anabolic steroid abuse. AAS were the fi rst identifi ed doping agents that have ergogenic eff ects and are on the International Olympic Committee's list of banned substances. This paper identify a) AAS increasing represent only one of many diff erent classes of agents it is important to used by recreational bodybuilders and by athletes in the 21st century b) their side eff ects c) their eff ects on sports performance c) phenomenon of polypharmacy.